2020
DOI: 10.1177/1475921720953846
|View full text |Cite
|
Sign up to set email alerts
|

Augmented reality for next generation infrastructure inspections

Abstract: This article introduces the use of emerging augmented reality technology to enable the next generation of structural infrastructure inspection and awareness. This work is driven by the prevalence of visual structural inspection. It is known that current visual inspection techniques have multiple sources of variance that should be reduced in order to achieve less ambiguous visual inspections. Emerging augmented reality tools feature a variety of sensors, computation, and communication resources that can enable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 28 publications
(24 reference statements)
0
14
0
1
Order By: Relevance
“…A proof of concept of application of AR in bridge monitoring presented by Yuan et al 350 An AR framework was presented by Athanasiou et al 351 It was shown that with the holographic reinforcement visualization, overall inspection time could be reduced, improving the efficiency in collecting and managing data. The enhancement to the visual inspection brought by AR and its integration with ML and DL is a promising technology for infrastructure inspection based on the review by Mascareñas et al 352 The enhancements brought by VR and AR can offer effective additions to other next-generation SHM applications, in particular, UAVs and smartphone-based systems, for both visualization and deployment measures. Human computer interaction can benefit from multisensory and interconnected media which can deploy SHM data for the operators, as well as users.…”
Section: Virtual Reality and Augmented Reality For Shmmentioning
confidence: 99%
See 1 more Smart Citation
“…A proof of concept of application of AR in bridge monitoring presented by Yuan et al 350 An AR framework was presented by Athanasiou et al 351 It was shown that with the holographic reinforcement visualization, overall inspection time could be reduced, improving the efficiency in collecting and managing data. The enhancement to the visual inspection brought by AR and its integration with ML and DL is a promising technology for infrastructure inspection based on the review by Mascareñas et al 352 The enhancements brought by VR and AR can offer effective additions to other next-generation SHM applications, in particular, UAVs and smartphone-based systems, for both visualization and deployment measures. Human computer interaction can benefit from multisensory and interconnected media which can deploy SHM data for the operators, as well as users.…”
Section: Virtual Reality and Augmented Reality For Shmmentioning
confidence: 99%
“…A proof of concept of application of AR in bridge monitoring presented by Yuan et al 350 An AR framework was presented by Athanasiou et al 351 It was shown that with the holographic reinforcement visualization, overall inspection time could be reduced, improving the efficiency in collecting and managing data. The enhancement to the visual inspection brought by AR and its integration with ML and DL is a promising technology for infrastructure inspection based on the review by Mascareñas et al 352…”
Section: Virtual Reality and Augmented Reality For Shmmentioning
confidence: 99%
“…(Data collection [83,142], visual inspection [7,38,84,86,[143][144][145][146], SHM [25,[147][148][149], safety inspection [8,45,150], road extraction [151] and pipeline positioning [152]) 9. 3D printing (Road repair [153]) 10.…”
Section: Application Of Information Technologies In Different Phasesmentioning
confidence: 99%
“…These include the headset's sensing platform, system, display and interface, and general properties including weight, durability, battery life, price, and availability. Mascareñas et al 27 gives an overview of these considerations used to make the device selection for this project. It was also important to consider the device manufacturer because development of AR applications varies depending on the platform.…”
Section: Hardwarementioning
confidence: 99%